Study of Lead (Pb) Distribution in Soil of Jetis District, Mojokerto Regency - Ananda Alfan Maulana; Bieby Voijant Tangahu; Anak Agung Gde Kartika; Kriyo Sambodho (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2019)
The increase in the percentage of land pollution in rural areas in East Java Province in 2011 to 2014 was caused by various factors. One of the factors that led to an increase in the percentage of land pollution was the increase in industrial activities in rural areas which made population growth and activity also increase.